Being at your best when your kids are at their worst : practical compassion in parenting - Payne, Kim John (Shambhala, 2019)
"A practical, meditative approach that can be used in the moment to help you stay calm and balanced when your child's behavior is pushing you to your limit--by the popular author of Simplicity Parenting. In difficult and challenging situations with our kids, every parent wants to react as much as possible in a way that reflects our family values and expectations. And yet when our children "push our buttons," we often find ourselves reacting in ways that we know are far from our principles, and even seem to further inflame a situation. Most distressing of all is when we feel ourselves falling into these predictable relationship patterns as they begin to happen. It gives us the sinking feeling of, "Oh no, here we go again." We know that when our children are at their worst, they need us to be at our best--or as close to it as we can get at the time. But how can we move from a "stress regress" to speaking in a voice that is warm, calm, and firm? Educator Kim John Payne offers techniques that simply but very directly shift these damaging patterns of communication and parental behavior. It is a grounded and practical tool that he has taught to numerous parents worldwide to: * Slow down the interaction * Give them a greater feeling of inner spaciousness * Be more in control of their reactions and the situation * Sense what their child's deeper needs are even though they are misbehaving * Respond in a way that gives the child a feeling of being heard and yet puts a boundary in place Being at Your Best When Your Kids Are at Their Worst is a technique that you can use in the moment to reframe the situation and help you respond effectively, appropriately, and with kindness"--